1994
DOI: 10.1016/0378-1097(94)90129-5
|View full text |Cite
|
Sign up to set email alerts
|

A role in cell-binding for the C-terminus of pneumolysin, the thiol-activated toxin of Streptococcus pneumoniae

Abstract: Cell binding of pneumolysin to target cells is an important step in the lysis of cells by this toxin. We sought to locate the cell-binding region of pneumolysin. Deletion of the six C-terminal amino acids decreased cell-binding activity by 98%. Furthermore, mutagenesis of an amino acid near the C-terminus decreased the cell-binding activity of full-length pneumolysin by 90%. The C-terminus of pneumolysin has an important role in cell-binding activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 14 publications
5
24
0
Order By: Relevance
“…The variant nature of the PLO undecapeptide may be required not only to properly align the undecapeptide sequence but also to maintain the structure of domain 4 in general. Support for the latter comes from minor substitutions at the C terminus of CDCs (Owen et al, 1994 ;Shimada et al, 1999), which disrupt the ability of these toxins to bind to cholesterol and host-cell membranes. Aligned with this final suggestion is the possibility that mutations introduced in this study result in the misfolding of domain 4, or indeed the entire PLO protein structure, leading to the reduction in haemolytic and cholesterolbinding activities.…”
Section: Discussionmentioning
confidence: 99%
“…The variant nature of the PLO undecapeptide may be required not only to properly align the undecapeptide sequence but also to maintain the structure of domain 4 in general. Support for the latter comes from minor substitutions at the C terminus of CDCs (Owen et al, 1994 ;Shimada et al, 1999), which disrupt the ability of these toxins to bind to cholesterol and host-cell membranes. Aligned with this final suggestion is the possibility that mutations introduced in this study result in the misfolding of domain 4, or indeed the entire PLO protein structure, leading to the reduction in haemolytic and cholesterolbinding activities.…”
Section: Discussionmentioning
confidence: 99%
“…12), it is likely that the decrease in ␤-sheet content produced by treatment occurs near these strands. It has been reported that C-terminal truncation of pneumolysin, another cholesterol-binding cytolysin, causes a loss of cell binding activity (17). It would be interesting to know whether this loss in the cell binding activity of pneumolysin is due to the loss of cholesterol binding activity, although conformational studies and molecular mass determination of the truncated species of pneumolysin would be required to draw a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the seven total tryptophan residues reside in domain 4, and three are located in the sequence of ECTGLAWEWWR (residues 430 -440), the longest conserved sequence among thiol-activated cytolysins (2, 3). From many efforts to achieve mutagenesis of this toxin family (13)(14)(15)(16)(17), it was shown that all mutations that inhibit cell binding activity reside in domain 4, suggesting that some region in domain 4 binds to membrane cholesterol upon binding to cells. This is consistent with our previous findings that a C-terminal tryptic fragment that contains predominantly domain 4 binds to cholesterol and to cholesterol-containing membrane (18).…”
mentioning
confidence: 99%
“…Membrane currents were recorded with an Axopatch 200 amplifier (Axon Instruments, Foster City, CA, USA) connected to a PC for data acquisition and subsequent analysis. Patch-pipettes were made from thick walled, filamented borosilicate glass capillaries, which were coated with Sylgard and fire-polished to give resistances of [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] MΩ. The holding potential was set to 0mV and a 1.6 s pulse to +40 followed by a 1.6 s pulse to -40 mV was applied every second throughout the recordings.…”
Section: Recording Conditionsmentioning
confidence: 99%